OPERATIONAL ANALYSIS OF ISLAMIC MARKETING MIX (9+1P): A QUALITATIVE NVIVO-BASED STUDY ON HAJJ SAVINGS IN ISLAMIC BANKING - Maratus Solihah; Nasrulloh Nasrulloh; Trischa Relanda Putra (Jesya, 2026)
This study addresses the limited operational explanation of the Islamic Marketing Mix 9+1P in Hajj savings products. Unlike previous studies that mainly examine its effect on customer satisfaction and loyalty, this study analyzes how sharia marketing values are practiced in daily banking services. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation, then analyzed through thematic coding with NVivo 14. The findings reveal that People, Process, and Pray are the most prominent elements in shaping customer trust and spiritual service value. This study contributes by positioning the 9+1P framework as an operational and spiritual service model for Islamic banking, especially in worship-oriented financial products.